Students’ Peer Feedback in EFL Writing Class of English Study Program - Saptenno, William Y.; Souisa, Threesje R. (Huele: Journal of Applied Linguistics, Literature and Culture, 2021)
As a part of writing process, feedback in writing place as the significant role and peer feedback is one type of feedback in classroom activities. This study was intended to find out the facts and expectation on peer feedback in writing classroom. A classroom-based research was employed as the research design and the participants were the students in writing 2 and writing 4 courses. Furthermore, Classroom observation, in-depth interview and review of related documents were designed to collect the data. The findings revealed that the application of peer feedback was not properly applied; it was more focused on the surface areas (grammatical errors, spelling and error punctuation) and neglected to the content and organization of writings. It could happen because the students lack of trainings and unavailability of rubric and guidelines provided in the writing classroom activities. For that reason, the students didn’t know the ways to provide meaningful and constructive feedback. They also have negative point of view about the peer feedback in writing courses. The students expected that providing writing rubric containing content and organization aspects precisely in giving feedback and guiding them step by step in taking and giving peer feedback should be considered by the lecturers for better improvement in the future.